PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN PT KERETA API INDONESIA (PERSERO) DAOP IV SEMARANG - Beni Sanjaya; Sudharto Prawata Hadi (Universitas Diponegoro, 2020)
Human resources is one important aspect of running a company. This is because the human resource can find new ideas transformed into actions so that organizational goals can be achieved. The company expects high employee performance, but in reality the employee performance at PT Kereta Api Indonesia (Persero) Daop IV Semarang is considered low, evidenced by the problem of lack of discipline in work, lack of work motivation, mistakes in working so it is less effective and efficient at work. This is certainly a significant problem for the company they are deals with will hamper the achievement of company goals.This study aims to identify the effect of leadership, work environment and organizational commitment on the performance of employees of PT Kereta Api Indonesia (Persero) Daop IV Semarang. The type of research used was explanatory research, samples taken are 95 respondents with the criteria of the employees of PT Kereta Api Indonesia (Persero) Daop IV Semarang, who had worked at least 1 year and were pleased to be interviewed and filled out the questionnaire. The sampling technique used was cluster sampling and the data collection technique used was a questionnaire. This study consisted of 4 variables, 22 indicators and 4 hypotheses. The analytical tool used is SPSS 16.0 for windows with validity test, reliability test, correlation coefficient test, determination coefficient, simple and multiple regression analysis and significance test (t test and F test). Based on the results of the analysis it can be concluded that leadership, work environment, and organizational commitment affect the performance of employees of PT Kereta Api Indonesia (Persero) Daop IV Semarang proven through multiple regression testing resulting in regression values of 0.013, 0.117 and 0.290. The advice given to the company is to improve the leadership of each manager by giving training and improving the physical work environment in the company PT Kereta Api Indonesia (Persero) Daop IV Semarang.